Pengaruh Ketinggian Lokasi Penanaman Terhadap Sifat Kimia dan Sensori Citarasa Kopi Robusta (Coffea canephora L) - Justisia Iriani Dewanti; Enny Purwati Nurlaili; Diah Kartikawati (Jurnal Agrifoodtech, 2023)
The chemical characteristics and sensory attributes of Robusta coffee are influenced by the environment of the coffee plant grows, one of the influencing factors is the altitude plantation locations. The aim of the research was to determine the effect of the land altitude of plantation location on the physicalchemical properties and sensory taste of Robusta coffee. This research used a Completely Randomized Design (CRD) with four (4) treatments based on altitude of the Robusta coffee plantation were: 650; 750; 379 and 545 above sea level. The parameters observed in this study were water content, ash content, pH value, caffeine content, and sensory characteristics (fragance, flavor, after taste, colour and overall). Data were analyzed using Analysis of Variance (ANOVA). The ANOVA result shows the Duncan’s Multiple Range Test (DMRT). Data was processed using the SPSS version 26 program. The results of the research show that altitude of plantation has a significant effect on the pH value, water content, caffeine content and are not significantly different. from the ash content. The caffeine content shows real differences between on altitude of planting, the highest caffeine content is shown in Robusta coffee grown at an altitude of 650 m above sea level at 2.49% and the lowest in Robusta coffee planted at an altitude of 545 m above sea level, at 1,77%. The robusta coffee taste sensory test showed that Robusta coffee grown at an altitude of 650 m above sea level was the most delicious coffee.